A comparison of abdominal ECG and Doppler ultrasound for fetal heart rate detection - Ibrahimy, Muhammad Ibn; Ali, M. A. Mohd; Zahedi, Edmond; Tsuruoka, Shinji (http://booksandjournals.brillonline.com/content/journals/10.1163/156855701321138950, 2001)
A fetal monitor has been developed for the measurement of the fetal and maternal heart rates from maternal abdominal electrocardiogram during pregnancy and labor for ambulatory monitoring. Developed algorithm of the fetal monitor is based on digital filtering, adaptive thresholding. statistical properties in the time domain and differencing of local maxima and minima. Five volunteers with low risk pregnancies, between 35 to 40 weeks of gestation and no evidence of labor, were studied for the fetal heart rate detection. A Doppler ultrasound fetal monitor was used to compare the accuracy of the measurement system. Results showed an average percent rms difference (PRD) of 5.32% in comparison with the reference ultrasound method. The fetal heart rates curve remained inside a +/- 5 beats/min limit relative to the reference ultrasound method for 84.1% of the time.